Effect of water pH on the early developmental responses in zebrafish (danio rerio) - Zahangir, MM; Haque, F; Mustakim, GM; Khatun, H; Islam, MS (Progressive Agriculture, 2015)
This experiment was conducted to evaluate the egg production performance in zebrafish (Danio rerio) in different pH treatments. Zebrafish were reared continuously 15 days in 3 different pH treatments like control (pH 6.8-7.4), acidic (pH 5.0-6.0) and basic (pH 9.0-10.0) media and then eggs were collected from them. Numbers of egg collection from the acidic and basic media were significantly varied from the control. Collected eggs from acidic, basic and control media were then incubated at different pH treatments ranging from pH 2.0-12.0. Significant differences were observed in hatching rate and time in control medium from two other different treatments. Progressive Agriculture 26:85-89, 2015